Implementation of the PBL Model Using PowerPoint Media to Improve Mathematics Learning Outcomes of First Grade Students at SD IT Riadaturrohman (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to improve student learning outcomes through the implementation of the Problem Based Learning (PBL) model assisted by PowerPoint media in Mathematics for Grade I students at SD IT Riyadhoturrohman. The research employs Classroom Action Research (CAR) conducted in two cycles. Each cycle consists of three meetings, following the stages of planning, implementation, observation, and reflection. The research subjects were 16 students from Grade I of SD IT Riyadhoturrohman. The Problem Based Learning model was chosen because it encouraged students to be actively involved in learning through solving contextual problems, while PowerPoint media was used to help visualize the mathematical concepts being taught. The results showed an improvement in students' learning outcomes from the pre-action stage to Cycle I, and a further increase in Cycle II. Additionally, students demonstrated improved participation, conceptual understanding, and teamwork skills. Thus, the implementation of the Problem Based Learning model assisted by PowerPoint media proved to be effective in improving the mathematics learning outcomes of Grade I students at SD IT Riyadhoturrohman.